Implementation of Dijkstra's Algorithm to Determine the Shortest Route in a City - Indah Purnama Sari; M. Fahri Fahroza; M.Ilham Mufit; Isnaini Faiz Qathrunad (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2021)
This study discusses the search for the shortest route from city A to city G using the Dijkstra algorithm based on distance traveled. Dijkstra's algorithm is one of the algorithms used to solve the shortest path and does not have a negative cost. The greedy strategy used in this algorithm is that each node in the graph will find the minimum value. This algorithm will look for a path with the minimum cost from one point to another. The purpose of this research is to understand the implementation of Dijkstra's algorithm on a graph to get the shortest route that is most optimal. The experimental results from city A to city G using Dijkstra's algorithm obtained the shortest route, which is 6 km with the route of city A - city C - city D - city E - city G.